Tsukamoto Method of Fuzzy Logic for Hotel Quality Determination - Pertiwi, Azira; Kesumaningtyas, Febby; Pratama, Rifaldo; Putra, Ilham Eka (CV. Publikasi Indonesia, 2024)
The rapid development of the hospitality industry has increased competition among hotels to provide the best services and facilities to attract customers. This study aims to determine hotel quality using the Tsukamoto method of fuzzy logic. The research measures the quality of hotel facilities, room classes, and prices, all of which contribute to visitor comfort. Data were collected from 10 hotels and processed using the Fuzzy Tsukamoto method to categorize hotel quality as either high or low. The analysis showed that variables such as hotel facilities and room class significantly influence the overall quality rating. The results indicated that hotels with complete facilities and higher room classes tend to score higher in quality. This research demonstrates that the Tsukamoto method provides an effective way to assess hotel quality based on multiple variables.